TCR signaling to NF-κB and mTORC1: expanding roles of the CARMA1 complex - Shi, Jian-hong (Mol Immunol, 2015)
Naïve T-cell activation requires signals from both the T-cell receptor (TCR) and the costimulatory molecule CD28. A central mediator of the TCR and CD28 signals is the scaffold protein CARMA1, which functions by forming a complex with partner proteins, Bcl10 and MALT1. A well-known function of the CARMA1 signaling complex is to mediate activation of IκB kinase (IKK) and its target transcription factor NF-κB, thereby promoting T-cell activation and survival. Recent evidence suggests that CARMA1 also mediates TCR/CD28-stimulated activation of the IKK-related kinase TBK1, which plays a role in regulating the homeostasis and migration of T cells. Moreover, the CARMA1 complex connects the TCR/CD28 signals to the activation of mTORC1, a metabolic kinase regulating various aspects of T-cell functions. This review will discuss the mechanism underlying the activation of the CARMA1-dependent signaling pathways and their roles in regulating T-cell functions.